Identification of the Glimepiride and Metformin Hydrochloride Physical Interaction in Binary Systems - Fitrianti Darusman; Taufik Muhammad Fakih; Gina Fuji Nurfarida (Borneo Journal of Pharmacy, 2021)
Glimepiride is often combined with metformin HCl as an oral antidiabetic in type II diabetes mellitus, which provides a complementary and synergistic effect with multiple targets for insulin secretion. Glimepiride includes class II of BCS, which solubility practically insoluble in water but high permeability, which will impact the drug's small bioavailability. In contrast, metformin HCl includes class III of BCS, which has a high solubility in water, but low permeability is absorbed approximately 50-60% in the digestive tract given orally. The co-crystallization method can be used to improve the glimepiride solubility properties and the permeability properties of metformin HCl by interrupting glimepiride with metformin HCl physically. This study aims to identify the physical interactions between glimepiride and metformin HCL using a thermal analysis of Differential Scanning Calorimetry (DSC) and then confirmed by a computational approach. Identifying the physical interactions between glimepiride and metformin HCL was carried out by plotting the melting points generated from the endothermic peaks of the DSC thermogram at various compositions versus the mole ratios of the two were further confirmed by the computational approach using PatchDock. The results of the phase diagram analysis of the binary system between glimepiride and metformin HCl show a congruent pattern, which indicates the formation of co-crystal or molecular compounds at a 1 : 1 mole ratio at 228°C. Computational approach results showed that the interaction between glimepiride and metformin HCl did not form new compounds but heterosinton formation that was stable in molecular dynamics simulations.